If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying H + -102 = 316 Reorder the terms: -102 + H = 316 Solving -102 + H = 316 Solving for variable 'H'. Move all terms containing H to the left, all other terms to the right. Add '102' to each side of the equation. -102 + 102 + H = 316 + 102 Combine like terms: -102 + 102 = 0 0 + H = 316 + 102 H = 316 + 102 Combine like terms: 316 + 102 = 418 H = 418 Simplifying H = 418
| a-7a+3= | | x^2-30-10=0 | | 4(7x+1)+12=44 | | 24x^2+8x+2=5 | | 3a+2a+7=17 | | 4(7x+a)+12=44 | | 7x-6=3x-20 | | -9+(-21)= | | X^4-7=9993 | | e^5x=y | | 2x+4x-70=0 | | 6x^2+24x-22=0 | | 3(x+2)+3=2x+10 | | 2x-9=63-10x | | ln(2x-1)=2ln(x) | | 2X-6=2X-5 | | 8ln(5x)=32 | | 6x+6=5x+13 | | x+v=w*2 | | x+5+2(x-1)=x+19 | | 3-5X=2-2X | | x+v=x*2 | | k(-10-7r)= | | .4= | | 12x+5=3+4x | | 4x^2+0x-100=0 | | v+x=x*2 | | 5x-6=x-8 | | 5(a+7b)-35b+5a= | | 63=2.1x | | 1.168=106x | | X-435=97 |